AB1083 Work impairment in patients experiencing musculoskeletal pain. (15th June 2017) - Higgins, NM; Cochrane, A; Rothwell, CJ; FitzGerald, O; Gallagher, P; Ashton, J; Breen, R; Brennan, A; Corcoran, O; Desmond, D
Abstract : Background: Many individuals with musculoskeletal disorders (MSD) continue to work. Little is known about those who remain occupationally active relative to those who are on sick leave, despite the clear potential for reduced productivity or work ability, and associated downstream effects. Objectives: To assess self-reported work impairment and its associations with psychosocial risk factors amongst workers seeking care for musculoskeletal pain. Methods: Recruitment took place in five Irish hospitals. Self-report questionnaires were used to assess risk of progressing to long-term sick leave and work disability (Örebro Musculoskeletal Pain Screening Questionnaire; ÖMPSQ), work ability, work impairment (WPAI) and work performance (WRFQ). Results: 155 patients (53.5% female; mean age =46.50 years (range 20 to 71)) completed the questionnaire. 25.2% (n=39) were at high risk of progressing to long-term sick leave and work disability according to the ÖMPSQ. 62.6% (n=97) were classified as functioning poorly according to the WRFQ; 52.3% reported having poor work ability (n=81). Higher work role functioning was associated with higher pain self-efficacy (OR =1.514); better work ability was associated with older age (OR =1.063) and poorer function (OR =0.929); absenteeism was associated with lower pain self-efficacy (OR =0.650) and higher return to work expectancy (OR =1.179). Presenteeism was associated with higher pain intensity (β =0.259) and lower pain self-efficacy (β = - 0.385). Conclusions: MSDs affect many individuals ability to work effectively. While all participants have managed to stay at work despite decreased levels of work ability and functioning, approximately a quarter are at high risk of progressing to long-term sickness absence. Interventions that attempt to improve mutable factors, such as pain self-efficacy, may help reduce the likelihood of work disability. Acknowledgements: This research is funded by the Health Research Board [RCQPS-2014–2]. Disclosure of Interest: None declared